Advanced Biosignal Processing and Diagnostic Methods - Hintermüller, Christoph (IntechOpen, 2016)
Personal health and well-being was and is important for all individuals. This includes the way people are living, what they do to stay healthy as well as a profound, well-informed diagnosis and appropriate treatment in case of disease. To achieve these goals, modern medicine is provided with a large variety of tools to assess a patient's health state and collect the information required for a proper diagnosis and treatment, which is tailored to the patient's needs. Many of these available tools use signals either generated by the human body, for example, electroencephalogram (EEG) and electrocardiogram (ECG), or by interacting with the human body while traversing it like microwaves or reflected visible light that is recorded by a video camera. The biosignals recorded by the available and newly developed methods have to be processed to extract the information about the patient's condition and, analyzed tissue and cells. This book presents a small selection of the recent developments in the field of biosignal processing. The covered diagnostic tools and methods include the assessment of respiratory state through gait analysis, the contactless monitoring of cardiovascular and respiratory parameters using microwaves, a non-linear approach to extract the fetal ECG from non-invasive abdominal recordings, identification of epileptic networks from pre-surgical neurophysiological recordings and an improved method to obtain and validate the copy number alterations parameter, which are considered an important marker in cancer classification.